FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PENGGUNA SISTEM INFORMASI AKUNTANSI BERBASIS KOMPUTER PADA PT.TRIO MOTOR BANJARMASIN - Rakhmi Ridhawati; Masrifani -; Noorfia Rosita Rani (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2016)
Abstract, This research was conducted in order to determine the influence of top management support, involvement penggun adalam system development process, engineering capabilities of personal information systems, training and education of users, and the formalization of development sistemi nformation on user satisfaction SIA on PT. Trio Motor Branch RE Martadinata Banjarmasin. Samples are employees who use computer-based accounting information systems as much as 43 people. The model of this research is multiple linear regression. Sources of data used in this study are primary data. The results showed that the support of management, user involvement in the development process of the system, personal technical capabilities, as well as training and education has no effect partially on user satisfaction SIA-based computer. Only formalization of system development affect the SIA user satisfaction based computer. While simultaneously, all the independent variables affect the dependent variable.